Current state of dialysis treatment and vascular access management in Japan. Issue 1 (May 2019) - Sato, Takashi; Sakurai, Hiroshi; Okubo, Kentaro; Kusuta, Risa; Onogi, Takeshi; Tsuboi, Masato
According to the data from the Japanese Society for Dialysis Therapy, the number of dialysis patients was about 330, 000 at the end of 2016. The mean age of newly initiated patients was 69.4 years and that of maintenance was 68.2 years. And, diabetic nephropathy is the most common primary disease, with an incidence rate of 43.2%. These results mean that the systemic vascular condition is getting worse. In spite of these backgrounds, the patients of 97.3% were treated by hemodialysis; therefore, careful management of vascular access is essential to better maintain the condition of patients. The Dialysis Outcomes and Practice Patterns Study shows that vascular access modalities are an important factor in determining prognoses of patients and that prognosis in Japan is one of the best worldwide. In Japan, the use of arteriovenous fistulae accounts for 95% of vascular access modalities. However, a statistic by Japanese Society for Dialysis Therapy suggests that the use of arteriovenous graft has been increasing. In 2005, Japanese Society for Dialysis Therapy Guidelines recommended percutaneous transluminal angioplasty be the first choice for the treatment of vascular access stenosis. Since then, percutaneous transluminal angioplasty has become an important procedure for long-term maintenance of the morphology and function of vascular access. In Japan, approximately 60% of percutaneous transluminal angioplasty are conducted by nephrologists and urologists; in addition, arteriovenous fistulae creation procedures are also performed by them. According to my private opinion, such conditions above show that even in the absence of standardized training on vascular access management, doctors on site perform their duties in an appropriate manner. However, the problems of how we evaluate the specificity in Japan and pass it down the generations still remain.